A Review of Analytical Methods for p-Coumaric Acid in Plant-Based Products, Beverages, and Biological Matrices - Ferreira, Paula Scanavez [UNESP]; Victorelli, Francesca Damiani [UNESP]; Fonseca-Santos, Bruno [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2019)
p-Coumaric acid (p-CA), also known as 4-hydroxycinnamic acid, is a phenolic acid, which has been widely studied due to its beneficial effects against several diseases and its wide distribution in the plant kingdom. This phenolic compound can be found in the free form or conjugated with other molecules; therefore, its bioavailability and the pathways via which it is metabolized change according to its chemical structure. p-CA has potential pharmacological effects because it has high free radical scavenging, anti-inflammatory, antineoplastic, and antimicrobial activities, among other biological properties. It is therefore essential to choose the most appropriate and effective analytical method for qualitative and quantitative determination of p-CA in different matrices, such as plasma, urine, plant extracts, and drug delivery systems. The most-reported analytical method for this purpose is high-performance liquid chromatography, which is mostly coupled with some type of detectors, such as UV/Vis detector. However, other analytical techniques are also used to evaluate this compound. This review presents a summary of p-CA in terms of its chemical and pharmacokinetic properties, pharmacological effects, drug delivery systems, and the analytical methods described in the literature that are suitable for its quantification.
Keywords: Analytical methods; bioavailability; drug delivery systems; high-performance liquid chromatography; p-coumaric acid; pharmacological effects